[PP.08.19] THE RELATIONSHIP BETWEEN OBESITY AND VISIT-TO-VISIT VARIABILITY IN SYSTOLIC BLOOD PRESSURE: A 30-MONTHS PROSPECTIVE FOLLOW-UP STUDY. (September 2017) - Stojanovic, S.; Ilic, M. Deljanin; Ilic, S.; Tasic, N.; Tasic, D.; Ilic, B.; Petrovic, D.; Dragisic, D.; Simonovic, D.
Abstract : Objective: The prevention of obesity and strategy for better patient compliance in efficient blood pressure control in obesity-related diseases are primary. The aim of this study was to clarify the change in parameters of obesity and systolic blood pressure (SBPV) during 30-months follow-up periods after starting the antihypertensive treatment and healthy lifestyle in hypertensive patients. Design and method: Prospective study included 300 randomly selected previously untreated hypertensive patients (148 men and 152 women, mean age 67.7 ± 9.8 years), who were divided according to body mass index (BMI more than or equal to 30 kg/m 2 ) to groups of obese (n = 216) and non-obese examinees (n = 84). The study comprised three visits during the follow-up period of 30-months. Obesity was defined according to both BMI and waist circumference (WC). SBPV for each examinee was evaluated at each visit using the standard deviation (SD) from 3 values of SBP. In order to estimate detailed evaluation of distribution SBPV quartiles of SBP-SD were formed. Results: The prevalence of overweight/obesity was very high according to both BMI and WC at the beginning of the study, and there was significant decrease in these values at the end of the study (72%, 64%, 22%, 19% p < 0.001). SBP and SBP-SD were significantly higher in the group of obese hypertensive patients than in the group of non-obese patients (129.41 ± 8.41 vs 119.04 ± 7.32 mmHg, 9.27 ± 5.28 vs 6.50 ± 3.52; p < 0.01). There was statistically stronger correlation between SBP-SD and BMI as the parameter of total obesity compared to WC as the parameter of central obesity (0.422 vs. 0.381, p < 0.01). The analysis showed statistically significant average decrease of SBP-SD for 9.1 mmHg, BP for 31/10 mmHg, BMI for 3.5 kg/m 2 and WC for 10 cm. The highest SBPV was recorded in the 4th quartile in obese patients (40.22 ± 7.14 mmHg). Conclusions: During the 30-months period after starting antihypertensive medication and healthy lifestyle with titrated dose of same class of antihypertensive drugs, reduction of body weight was associated with reduction of blood pressure values, and lower value of blood pressure variability.